Kurikulum Pendidikan Jasmani Olahraga di Perguruan Tinggi dan Implementasinya - R. Agung Purwandono Saleh (Journal on Education, 2024)
The purpose of this study was to determine the Physical Education and Sports Curriculum in Higher Education and its Implementation. This research was conducted at UPN "Veteran" Yogyakarta. This research is included in the type of qualitative research. The method used in this study is a survey. Data collection techniques in this study used interviews, observations and documentation. The results of this study are the physical education and sports curriculum in Higher Education and how it is a form of appreciation and high commitment of Higher Education to sports development efforts as part of maintaining health and improving physical fitness as well as improving sports achievements among students. Supporting factors for the implementation of physical education and sports in Higher Education include the need for a curriculum with competent teaching staff including coaches and the role of relevant sports sciences and sports activity units that accommodate student sports activities. The conclusion of this study is that the Physical Education and Sports Curriculum in Higher Education has benefits for health through the goals of physical fitness and improving student sports achievements. The existence of the physical education and sports course curriculum, students are encouraged to be actively and sustainably motivated to carry out physical activities to stay healthy. The supporting function of student sports activities requires a teaching staff who is also capable as a trainer and coach who is able to help bring out all the potential of students to maintain achievements or to improve achievements in the field of sports. As a form of expressing student potential through the process of training and coaching, not just through the form of a teaching and learning process in theory or practice that only fulfills the goal of improving physical fitness. An important role for teaching staff for physical education and sports courses is chosen by someone who in addition to having teaching competence also has the competence to train and foster students in the chosen sport to improve their optimal achievements.